Gauge theory of elementary particle physics - Cheng, Ta-Pei; Li, Ling-Fong (Oxford University Press, 2024)
Students of particle physics often find it difficult to locate resources to learn calculational techniques. Intermediate steps are not usually given in the research literature. To a certain extent, this is also the case even in some of the textbooks. In this book of worked problems we have made an effort to provide enough details so that a student starting in the field will understand the solution in each case. Our hope is that with this step-by-step guidance, students (after first attempting the solution themselves) can develop their skill, and confidence in their ability, to work out particle theory problems.